The rational framework of scientific thinking in islamic tradition - Shogar, Ibrahim (Universiti Sultan Azlan Shah (USAS), 2016)
The scientific thinking in Islamic tradition is inspired by the genuine sources of Divine revelation. It is mode of a systematic inquiry that triggered by the principles of the Islamic worldview and guided by the common thought of Muslim intellectual’s community. Both, the proper understanding of the sources and conscious application of the principles of the worldview are essential to maintain the spirit of scientific thinking. The terminal goal of systematic inquiry in Islamic tradition is to utilize forces of the temporal for the Absolute, but achieving such a noble goal is impossible without proper understanding of both the natural and human phenomena. This paper investigates the conceptual and rational frameworks of scientific thinking in Islamic tradition. Utilizing the analytic approach of qualitative method, the paper investigates both the cognitive (epistemic) and conventional (social) aspects of scientific thinking based on Qur`anic perspective.